2021
DOI: 10.5852/ejt.2021.740.1281
|View full text |Cite
|
Sign up to set email alerts
|

Two new tanaidaceans (Crustacea: Peracarida) from Portuguese submarine canyons (NE Atlantic, West Iberian Margin)

Abstract: The Tanaidacea are ubiquitous and amongst the most abundant taxa in the deep sea. However, their diversity in submarine canyons remains largely unknown. Here, two new species and a new genus of Paratanaoidea are described. Paranarthrura cousteaui sp. nov. is distinguished by the combination of the following characters: post-cheliped sclerites not fused, presence of one seta in the maxilliped endite, one long midventral seta in cheliped, one penicillate seta in the basis of pereopods 4–6, uropod endopod bi-arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 729 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The biodiversity of Tanaidacea in submarine canyons is largely understudied; however, the recent works available included the discovery of new taxa that provided significant information for the understanding of the systematics of the group. For instance, Sganga & Roccatagliata (2016) described Deidamiapseudes, a genus of an uncertain position between the Apseudidae and Metapseudidae Lang, 1970, andGarcía-Herrero et al (2021)…”
Section: Ecology and Biogeographymentioning
confidence: 99%
See 1 more Smart Citation
“…The biodiversity of Tanaidacea in submarine canyons is largely understudied; however, the recent works available included the discovery of new taxa that provided significant information for the understanding of the systematics of the group. For instance, Sganga & Roccatagliata (2016) described Deidamiapseudes, a genus of an uncertain position between the Apseudidae and Metapseudidae Lang, 1970, andGarcía-Herrero et al (2021)…”
Section: Ecology and Biogeographymentioning
confidence: 99%
“…Studies have shown that tanaidaceans are among the dominant taxa in benthic macrofaunal assemblages in submarine canyons (e.g., Cunha et al 2011;Gunton et al 2015); however, to date only two studies make species-level references to Tanaidacea: García-Herrero et al (2021) covering three canyons in the Portuguese margin, and Sganga & Roccagliata (2016) in Mar de Plata Canyon (SW Atlantic). Although Lacaze-Duthiers Canyon is one of the most studied canyons in the Mediterranean Sea (e.g., Got & Stanley 1974;Vénec-Peyré 1990;Fabri et al 2014;Meistertzheim et al 2016), our knowledge of the soft-bottom macrofauna community composition is scarce.…”
Section: Introductionmentioning
confidence: 99%